Movement Disorders in Clinical Practice - Chaudhuri, K. Ray.; Ondo, William; SpringerLink (Online service) (London : Springer London, 2010)
Movement disorders attack the part of the brain that controls our movements, they are a complex group of disorders, spanning all aspects of neurological illnesses. Such disorders are widespread, often destroying the independence of those affected. Movement Disorders in Clinical Practice provides a concise, practical overview of the diagnosis, treatment and management of patients with these debilitating conditions, including a brief evaluation of ongoing clinical trials. Edited by two key international movement disorder experts, chapters cover: Parkinson$1 (Bs disease Parkinsonian syndromes Dystonia Tremor Restless legs syndrome An overview of other movement disorderss
Contents -- 1. Parkinson$1 (Bs disease - Introduction - Epidemiology, incidence, and prevalence - Risk factors - Genetic factors - Pathophysiology - Symptoms and signs - Confirmation of diagnosis - Management of Parkinson$1 (Bs disease - Neuroprotection - Stereotactic thalamotomy and deep brain stimulation - Transplant therapies - Nondopaminergic drug therapy - Specialist nursing care - Cost of care - Mortality and prognosis - Conclusions -- 2. Parkinsonian syndromes - Introduction - Neurodegeneration-linked parkinsonism - Multiple system atrophy - Progressive supranuclear palsy - Dementia with Lewy bodies - Corticobasal degeneration - Vascular pseudoparkinsonism - Other parkinsonian syndromes - Management - Conclusions -- 3. Dystonia - Definition - Classification - Location - Pathophysiology - Epidemiology - Genetics - Signs and symptoms - History and investigations - Treatments - Conclusions -- 4. Essential tremor - Introduction - Tremor subtypes and differential diagnosis - Physical examination and clinical evaluation - Epidemiology and neuropathology - Treatment -- 5. Restless legs syndrome -Restless legs syndrome - Periodic limb movements of sleep - RLS in children - Diagnostic evaluation - Epidemiology - Genetics - Pathophysiology - Treatment -- 6. Other movement disorders - Drug-induced movement disorders - Tics and Tourette$1 (Bs syndrome - Chorea, ballismus and athetosis - Myoclonus - Ataxia - conclusions.s
Keywords: Medicine; Emergency medicine; Family medicine; Neurology; Medicine & Public Health; Neurology; General Practice / Family Medicine; Emergency Medicine